PENGGUNAAN POSTER INFOGRAFIS PADA PEMBELAJARAN IPA MATERI SISTEM PERNAPASAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP KELAS VIII - Saputra, Ardiansyah Dharma; Hidayati, Siti Nurul (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research was conducted to determine the increase in student learning outcomes using infographic posters in natural science learning. This type of research used pre-experimental one group pretest posttest design. The research subjects used in this study were 21 students of class VIII-H. Data collection techniques in this research used observation, questionnaires, and tests. The research instrument consisted of learning implementation observation sheets, student response questionnaire sheets, student knowledge test sheets. The results of this study are: (1) The implementation of the natural science learning on the respiratory system material as a whole has been carried out in the "Good" category; (2) The average percentage of student responses to the use of infographic posters in natural science learning as a whole obtains a percentage of 88% in the "Very Good" category; (3) Student learning outcomes in the cognitive aspect show that the use of infographic posters in natural science learning increases learning outcomes with an average percentage score of 65% in the category "Effective enough".